Mechanisms of Impact of Alnus ferdinandi-coburgii Odor Substances on Host Location of Tomicus yunnanensis - Jingyi Bo; Wen Li; Xiangyi Li; Zongbo Li; Xiangzhong Mao; Bin Yang; Ning Zhao (Insects, 2025)
In the chemosensory system of insects, odorant-binding proteins (OBPs) and odorant-degrading enzymes (ODEs) play a role in the host location process. This study identified and analyzed chemosensory-related genes from the transcriptomes of different tissues of male and female adults of Tomicus yunnanensis. Subsequently, host odorants from Pinus yunnanensis and non-host odorants from Alnus ferdinandi-coburgii were used to treat the adults of T. yunnanensis to clarify the gene expression changes in the insects and, combined with molecular docking, to explore the mechanism of the non-host odor interfering with the host localisation of T. yunnanensis. A total of 137 chemosensory-related genes were obtained, among which TyunOBP6 was specifically highly expressed in the antennae of T. yunnanensis; TyunCYP4G2 and TyunCYP6DF1 were highly expressed in the remnants of T. yunnanensis, selected as key genes for further research. The odor interference experiment results show that both host and non-host odorants caused up-regulation of TyunOBP6 in antennal expression, and significant changes in the expression of TyunCYP4G2 and TyunCYP6DF1 in the remnants were also observed. The molecular docking results indicate that non-host compounds could compete with host compounds for protein binding sites. The non-host odor of A. ferdinandi-coburgii can interfere with TyunOBPs and TyunCYPs in T. yunnanensis and affect their host localization.